A STUDY ON ARTIFICIAL INTELLIGENCE FOR A SUSTAINABLE FUTURE IN INDIA: OPPORTUNITIES AND CHALLENGES - Swetha Golla; T Sanjay Kumar, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Artificial intelligence (AI) holds significant potential to promote sustainability in India and address key challenges in areas such as energy, agriculture, waste management, and climate change. However, its adoption presents unique opportunities and challenges within the Indian context. This article explores how AI can contribute to sustainable development by optimising renewable energy integration, enhancing precision agriculture, and enabling intelligent urban planning. At the same time, it examines barriers such as high computing costs, data shortages, ethical concerns, and inadequate digital infrastructure. The study highlights India’s growing AI initiatives, including government policies, private-sector innovations, and state-level guidelines, while emphasizing that it requires energy-efficient AI models and better system integration. The paper concludes that coordinated efforts by policymakers, researchers, and industry leaders are crucial to harness the full potential of AI for a sustainable future in India.